2013
DOI: 10.1007/s12639-013-0250-4
|View full text |Cite
|
Sign up to set email alerts
|

Histological patterns of the intestinal attachment of Corynosoma australe (Acanthocephala: Polymorphidae) in Arctocephalus australis (Mammalia: Pinnipedia)

Abstract: The mucosal attachment pattern of Corynosoma australe in the intestines of Arctocephalus australis is described. Normal and abnormal tissue were sampled from 32 hosts to be submitted to histological routine protocol to embedding in paraffin and permanent mounting in balsam. Corynosoma australe shows three different degrees of body depth intestinal attachment (BDINA-1-3). BDINA-1: it is exclusive of the small intestine and the parasite attaches on the villi; BDINA-2: parasite affects the Lieberkühn crypts in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
(30 reference statements)
1
14
0
Order By: Relevance
“…Likewise, in fully attached individuals of Corynosoma spp. there are observations of worms with the proboscis fully [ 15 ] or partially [ 16 ] everted. It is therefore possible that the relatively long proboscis typical of Corynosoma spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, in fully attached individuals of Corynosoma spp. there are observations of worms with the proboscis fully [ 15 ] or partially [ 16 ] everted. It is therefore possible that the relatively long proboscis typical of Corynosoma spp.…”
Section: Discussionmentioning
confidence: 99%
“…9 b). Moreover, the host’s tissue is so strongly pulled upwards by the DNRs that a crater is frequently formed during deep attachment [ 2 , 16 ]. This elevation of the substratum often traps host tissue between the hooks of the proboscis and the spines on the opposite disk wall, “...as though staples had been applied” on it [ 2 ] (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the observed histological responses to the intestinal parasites mainly comprised a thin or absent mucosa and mild infiltration of lymphocytic cells and eosinophils close to the attachment sites of the parasites. Other studies have found only a slight intestinal inflammatory response to Corynosoma in seals and the attachment pattern of Corynosoma observed in South American fur seals significantly reduced the thickness of the intestinal mucosa [39,40]. Minor intestinal lesions (erosions less than 10 mm in diameter) in Baltic grey seals are supposedly unavoidable due to the attachment of the parasites, although larger ulcerations are likely to be pathological.…”
Section: Discussionmentioning
confidence: 91%
“…This variety of responses could be attributed to several causes: 1) the time that the parasites had been affecting the host, since heterophiles are the first line of attack against the parasite; 2) the extent of the lesion associated with the size of the entire parasite or fixation structures; 3) type of fixation structures, 4) group of parasite or 5) by bacteria or fungi inoculated in the cuticle during the process of fixation to the organ ( Dunstand et al, 2019 ), which stimulate the appearance of heterophiles ( Phillips et al, 1980 ). According to the classification of the lesions established by Silva et al (2014) , who studied the damage caused by the acanthocephalan Corynosoma australe in mammals, P. constrictum and Filicollis sp., the 2 species found in the waterfowl, could be located in the grade II, due to the presence of necrosis, destruction of villi and Lieberkühn crypts and by the low lymphocyte infiltration; the only differences with respect to the study by Silva et al (2014) , is the presence of heterophils and giant cells in our samples. This type of reaction suggests that the 2 species had been attached to the intestine for a long time, so the host's immune system developed this response, preventing the worms from causing more damage, or that the helminths stimulated the proliferation of fibroblasts around them to evade the immune system.…”
Section: Discussionmentioning
confidence: 99%